TRANSFORMASI DUNIA KERJA ERA DIGITAL(PERGESERAN DARI PEKERJA KANTORAN KEPEKERJA FREELANCE BERDASARKAN TEORI PERUBAHAN SOSIAL) - Amelia Natasya Saragih Amel; Agusmidah Agusmidah; Dedi Harianto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology has had a significant impact on the patterns and structure of the modern workforce. Conventional work systems that rely on physical presence in the office are now shifting towards flexible, digitally-based work patterns, such as freelance or the gig economy. This study aims to analyze the transformation of the workforce in the digital era, the driving factors behind the shift from office workers to freelance workers, and to examine this phenomenon through the theory of social change. The method used is descriptive qualitative research with a literature study approach. The results of the study indicate that technological changes, time flexibility, and the need for work autonomy are the main factors driving this shift. Based on the theory of social change, this phenomenon represents a form of societal adaptation to technological advancements and the demands of globalization. The government is expected to develop digital employment policies to ensure the welfare of freelance workers.Thus, the transformation of the world of work in the digital era is not merely a technical change, but also reflects a shift in the social paradigm in understanding productivity, careers, and well-being. The government and relevant institutions are expected to be able to formulate inclusive, adaptive, and sustainable digital labor policies so that the welfare and social protection of freelance workers can be ensured fairly and equitably.